Ocular characteristics of patients with cerebral palsy - Guven, Soner; Avni Uludag, Huseyin; Kucukevcilioglu, Murat; Mehmet Mutlu, Fatih (Annals of Medical Research, 2021)
Aim: The purpose of this study is to report the ophthalmic characteristics and treatment results of our cerebral palsy (CP) patients. Materials and Methods: We explored the charts of 62 CP patients who were followed by our tertiary referral pediatric ophthalmology and strabismus department between 1998-2018 retrospectively. Patient demographics, strabismus type, preoperative deviation, type of surgery, visual acuities (VA), fundus findings, first surgery time, additional surgeries and anomalies and follow-up time were recorded. Results: Mean age and follow-up time were 34.1 and 42.6 months respectively. Most of the subjects (80.6%) had bilateral VA less than 20/200. The ratio of patients without fixation and follow was 11.2% in right eye and 14.5% in left eye. Fifty eight percent of patients had normal fundus findings. The most leading finding was bilateral optic disc pallor in abnormal fundus patients (33.8%). Fifty-six (90.1%) patients had strabismus (esotropia (ET) (50%), exotropia (XT) (35.5%), vertical deviation (4.8%). Mean horizontal deviation was 25.64±8.41 (8-40) prism diopter (PD) in ET and 25.4±9.39 (12-40) PD in XT. We performed strabismus surgery to 20.9% of patients. The most frequent surgery type was bilateral medial rectus recessions. Mean first surgery time was 35.6 months. Four (30.7%) patients who had previous strabismus surgery needed additional surgery. The most frequent additional surgery types were medial rectus advancement (50%) and inferior oblique myectomy (50%). Prematurity (19.3%), epilepsy (12.9%) and corpus callosum dysplasia and periventricular leukomalacia (12.9%) were the leading encountered additional anomalies. Conclusions: CP patients are mostly accompanied with esotropia. The management of CP patients may be challenging due to need of additional surgeries.